385 California heat illness prevention study (CHIPS) in immigrant Latino farm workers. (11th October 2013) - Schenker, B; Mitchell,; Wadsworth,; Jones,
Abstract : Objectives: To quantify the contributions of work intensity and ambient heat to the risk of heat illness in field labourers working with diverse crops. Methods: Field workers were assessed throughout a single daytime work shift. Body weight and blood osmolality changes, continuous heart rate and core body temperature (using ingested telemetry) were recorded. Personal and stationary (area) ambient air temperature and relative humidity were measured using individual data loggers and weather stations. Workers were questioned about their current and historical experiences with field work in the heat. Results: One-hundred workers were assessed between late June and August 2012 on seven farms in the California Central Valley. Thirteen were female, mean age was 36.8 (SD = 11.9) years. Ninety-four percent were born in Mexico, the remainder in the USA, and over 95% of the workers identified as Latino. Educational level was low; 47% had attended ≤ 6 years of school. Twenty-two percent lost over 1.5% of their original body weight (ACGIH suggested criteria for increased risk of dehydration), 80.2% increased serum osmolality, with 21% increasing ≥ 3%. Males lost significant weight (-0.56 kg, 95% CI -0.40 to -0.73 kg) as did those whose blood osmolality increased (-0.59 kg, 95% CI -0.34 to -0.85 kg). Associations will be assessed between heart rate, task, crop, ambient conditions and core body temperature. Conclusions: Field workers exhibited reduced hydration status over their work shift. Combined physiological and survey data may allow susceptibility to heat illness in summertime agricultural workers to be quantified.